Enhancing the Performance of Piezoelectric Vibration Energy Harvester Through Adjustments in the Geometric Configuration and the Volume of Additional Magnets - Kumar K.; Tyagi A. (My University, 2025)
Purpose: Recent studies on conventional multi-stable piezoelectric vibration energy harvesters (CM-PVEH) have improved voltage output and operational frequency range by maintaining equal volumes for equidistant additional magnets. The piezoelectric vibration energy harvester (PVEH) performance can be further improved by manipulating the parameters that affect the magnetic field between the tip magnet and additional magnets. This paper presents a detailed investigation into the impact of geometric configurations of additional magnets and the volume of side magnets on the voltage output and power of the PVEH system under low-intensity base excitation of up to 1 g in the frequency range of 5 to 22 Hz. Methods: A theoretical model of the PVEH system is developed using Euler–Lagrange equations to derive the coupled electromechanical equations. These equations are solved using the Runge–Kutta method in MATLAB to determine the system's response. The model's performance is validated and analysed through comprehensive experiments. Results: Experimental results demonstrate a substantial influence of geometric configuration on both voltage and power output in broader frequency range. With equal-sized side magnets, the improvement amounts to 9.46 times higher, and for small-sized side magnets, the configuration achieves a remarkable 10.25-fold increase in maximum power output compared to equivalent conventional configurations. Conclusions: Both numerical simulations and experimental observations underscore the superior performance of the PVEH system by modifying the relative gaps between magnets and their volumes. The findings contribute valuable insights into optimising PVEH designs for enhanced energy harvesting. © Springer Nature Singapore Pte Ltd. 2025.